Mesdames et Messieurs Les Proviseurs: Principals Address Structural Inequalities in a Diverse High School. Issue 1 (September 2017) - Bense Ferreira Alves, Celia; Nguyen Duc Long, Michel
This article examines how high school principals in France work to change the negative effects that the country's academic tracking system brings to students from immigrant and working-class backgrounds. The tracking system tends to relegate these students to lower vocational tracks that do not prepare them well for the labor market and tend to reinforce their social marginalization. The authors—one a sociologist and the other a school principal—describe a comprehensive, diverse lycée in a suburb of Paris where administrators are addressing the multiple impacts of tracking on their students by enabling some to change tracks and providing others the support they need to succeed when facing challenges at school and in their neighborhoods. The description and analysis of daily life at school not only illuminates what is distinctive about the French system but also lays out strategies and practices that make the school environment more egalitarian.